Comparative evaluation of result after internal fixation of clavicle fracture with titanium elastic nail and plate - Dr. Vikrant Sharma, Dr. Anand Kumar Goyal, Dr. Shashank Tayal, Dr Ashish Gupta, Dr. Siddharth Tayal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: This study evaluated the outcomes of using titanium elastic nail (TEN) fixation in combination with plate fixation to treat midshaft clavicle fractures. Methods: 60 patients with displaced midshaft clavicle fractures were randomly assigned to either Group A (TEN fixation) or Group B (Plate fixation). At six weeks, three months, and six months following surgery, a number of factors were assessed. Surgical duration, intraoperative hemorrhage, radiological union time, functional results, and complications were among them.